MODERATE ISLAMIC EDUCATION CURRICULUM DESIGN: REALIZING TOLERANCE AMIDST SOCIAL DIVERSITY IN THE ERA OF SOCIETY 5.0 - Ach. Sayyi; Saepudin Mashuri; Afandi Afandi; Abdul Salam Hamood Ghaleb Alanesi (Jurnal Konseling Pendidikan Islam, 2025)
Moderate Islamic education with a tolerant curriculum amidst diversity is crucial in shaping a generation that not only understands religious teachings but also values social and cultural differences. In Indonesia, which is rich in pluralism, the development of an Islamic education curriculum that prioritizes moderation and tolerance is a key challenge in fostering social peace. This study aims to recommend a model for designing Islamic education curricula that instills values of moderation, interfaith tolerance, and respect for differences. The approach used in this study is qualitative, with a library research method, relying on the collection of relevant literature to explore the concepts and best practices in moderate curriculum design. The results of the study indicate that an Islamic education curriculum that emphasizes moderation and tolerance must integrate materials on religious pluralism, apply dialogical and collaborative teaching methods, and include assessments based on attitudes of tolerance toward differences. Additionally, the curriculum should prioritize teaching universal values such as peace, justice, and mutual respect. Collaboration between the government, educational institutions, and society is essential to realizing an adaptive, inclusive Islamic education curriculum that can create a more peaceful and harmonious society amidst diversity.